350 Incidence and Long-term Health Care Utilization Associated with Pseudomeningocoele Repair Following Vestibular Schwanomma Resection: A National Database Analysis. (1st April 2022) - Sharma, Mayur; Aljuboori, Zaid; Wang, Dengzhi; Ugiliweneza, Beatrice; Boakye, Maxwell; Williams, Brian Jeremy; Andaluz, Norberto O.
Abstract : INTRODUCTION: Long-term health care utilization of patients who developed CSF leak and Pseudomeningocoele (PSM) following Vestibular Schwanomma (VS) surgery is not well defined. METHODS: MarketScan database were queried using the International Classification of Diseases, Ninth and Tenth Revisions and Current Procedural Terminology 4, from 2000 to 2018. We included patients 18 years of age with PSM diagnosis with at least 2 years of continuous enrollment. Outcomes analyzed were hospital admissions, outpatient services, medication refills and their associated payments. RESULTS: Of 1460 patients, 96.6% (n = 1411) had no PSM following surgery for VS, 2.4% (n = 35) were in s-PSM and only 0.95% (n = 14) were in ns-PSM cohorts. Patients in the s-PSM cohort incurred higher hospital readmission rate, outpatient payments compared to those in nd-PSM and ns-PSM cohorts at 6 months, 1-year and 2 –years following the following VS resection. At 1-year following VS resection, median combined payments for s-PSM cohort were $74, 683 compared to $42, 664 for ns-PSM and $9476 for nd-PSM cohort, p < 0.0001 Similarly, at 2-years, median combined payments median combined payments for s-PSM cohort were $83, 351 compared to $63, 942 for ns-PSM and $18, 839 for nd-PSM cohort, p < 0.0001. CONCLUSION: Patients in s-PSM cohort incurred 8 times and 4.4 times the combined payments at 1- and 2-years respectively compared to nd-PSM cohort. Also, patients in ns-PSM cohort incurred 4.5 times and 3.4 times the payments compared to nd-PSM cohort.